1994
DOI: 10.1093/bja/73.3.293
|View full text |Cite
|
Sign up to set email alerts
|

Does training on an anaesthesia simulator lead to improvement in performance?

Abstract: We have used the Leiden anaesthesia simulator, which makes use of a standard anaesthesia machine and monitors, and realistically simulates the anaesthesia work place. After obtaining informed consent, 28 anaesthetists and anaesthesia trainees in one hospital took part in the study. All participants were exposed to a pre-scripted simulated "control" scenario of anaphylactic shock (phase 1). The sessions were videotaped and the performances of individual participants were evaluated using a standardized scoring s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
115
0
12

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(133 citation statements)
references
References 11 publications
4
115
0
12
Order By: Relevance
“…Additionally, management of infrequent events such as failed intubation with failed ventilation can be practised without risk to live patients. Although largely unproven, practising these skills within this context is felt to improve technical, cognitive and team-working performance if similar situations are encountered in real life [104]. On this basis, this modality has been incorporated into several airway simulation courses in the UK, providing a hybrid of theory, practical skills stations and participation in airway scenarios in a recreated medical environment (see below).…”
Section: High Fidelity Platform Simulation Trainingmentioning
confidence: 99%
“…Additionally, management of infrequent events such as failed intubation with failed ventilation can be practised without risk to live patients. Although largely unproven, practising these skills within this context is felt to improve technical, cognitive and team-working performance if similar situations are encountered in real life [104]. On this basis, this modality has been incorporated into several airway simulation courses in the UK, providing a hybrid of theory, practical skills stations and participation in airway scenarios in a recreated medical environment (see below).…”
Section: High Fidelity Platform Simulation Trainingmentioning
confidence: 99%
“…The repetition of simulation sessions may be useful for improving adherence to algorithms in general. 11 However, given the costs of simulation teaching and displacement of experienced physicians from their workplace, there is a definite need for a more reliable and effective way to approach these expert participants.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, based on a previous study involving simulators, 11 we hypothesized that approximately 50% of the participants would make at least one major deviation from the ASA difficult airway algorithm at baseline (1st CICV). A sample size of 40 would provide 81.6% power to detect a minimum 30% decrease in the proportion of participants committing major deviations from the first to the second session, considering an a error of 0.05.…”
Section: Sample Size and Statistical Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies on the effectiveness of simulation-based training have used performance during simulated critical events as outcome measures, in large part due to the challenges of measuring performance in clinical settings. Chopra et al 49 showed that anesthesiologists trained to manage malignant hyperthermia with a full-body mannequin simulator responded more quickly, deviated less from accepted guidelines, and performed better in handling a subsequent simulated malignant hyperthermia than residents who did not receive the training. Yee et al 50 showed that a single simulation session constructed around an ACRM-type course improved non-technical skills (i.e., decision-making, situation awareness, and interpersonal skills) of residents during a simulated anesthesia crisis.…”
Section: Changes In Learner Perceptionsmentioning
confidence: 99%